Using Position‐Based Dynamics for Simulating Mitral Valve Closure and Repair Procedures. (21st December 2021) - Walczak, Lars; Georgii, Joachim; Tautz, Lennart; Neugebauer, Mathias; Wamala, Isaac; Sündermann, Simon; Falk, Volkmar; Hennemuth, Anja
Abstract: To achieve the best treatment of mitral valve disease in a patient, surgeons aim to optimally combine complementary surgical techniques. Image‐based in silico simulation as well as visualization of the mitral valve dynamics can support the visual analysis of the patient‐specific valvular dynamics and enable an exploration of different therapy options. The usage in a time‐constrained clinical environment requires a mitral valve model that is cost‐effective, easy to set up, parameterize and evaluate. Working towards this goal, we develop a simplified model of the mitral valve and analyse its applicability for the sketched use‐case. We propose a novel approach to simulate the mitral valve with position‐based dynamics. The resulting mitral valve model can be deformed to simulate the closing and opening, and incorporate changes caused by virtual interventions in the simulation. Ten mitral valves were reconstructed from transesophageal echocardiogram sequences of patients with normal and abnormal physiology for evaluation. Simulation results showed good agreements with expert annotations of the original image data and reproduced valve closure in all cases. In four of five pathological cases, abnormal closing behaviour was correctly reproduced. In future research, we aim to improve the parameterization of the model in terms of biomechanical correctness and perform a more extensive validation. Abstract : We develop a simplified Position‐based Dynamics model of the mitral valve and analyze its applicability for simulating valve closure and repair procedures in a clinical decision support scenario. A time‐constrained clinical environment requires simulation models that are accurate, cost‐effective, interactive, easy to set up, parameterize, and evaluate.